1980
DOI: 10.1002/j.1551-8833.1980.tb04516.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Technique for Measurement of pH for Corrosion Control Studies and Water Not in Equilibrium With the Atmosphere

Abstract: Water quality analyses are very sensitive, and it is critical that the pH be measured as accurately as possible. This technique was developed after the authors observed that many water utility and research laboratory personnel follow poor techniques for determining pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…These showed that if the pH was only slightly different (6.44), both total alkalinity and DIC values became consistent well within the laboratory's documented analytical error. This follows well with the expected direction of the bias of a high‐CO 2 water exposed to the atmosphere during even a good field pH measurement (Schock et al, 1980) and with earlier measurements of the raw water at PCWD during exploratory testing. Therefore, when the estimated pH of 6.44 (rather than 6.6) is used, CO 2 removal efficiency was 96%, almost exactly what would be expected from the design of the diffused bubble system and predicted by general carbonate equilibria expressions commonly applied to aeration (Lytle et al, 1998a; Lytle et al, 1998b; Lytle et al, 1998c).…”
Section: Water Quality and Operational Effectssupporting
confidence: 88%
“…These showed that if the pH was only slightly different (6.44), both total alkalinity and DIC values became consistent well within the laboratory's documented analytical error. This follows well with the expected direction of the bias of a high‐CO 2 water exposed to the atmosphere during even a good field pH measurement (Schock et al, 1980) and with earlier measurements of the raw water at PCWD during exploratory testing. Therefore, when the estimated pH of 6.44 (rather than 6.6) is used, CO 2 removal efficiency was 96%, almost exactly what would be expected from the design of the diffused bubble system and predicted by general carbonate equilibria expressions commonly applied to aeration (Lytle et al, 1998a; Lytle et al, 1998b; Lytle et al, 1998c).…”
Section: Water Quality and Operational Effectssupporting
confidence: 88%
“…The pH was measured using a series of benchtop pH/ion‐selective electrode meters under computer control to report stability. Measurements of pH used a closed‐system technique with repetitive re‐equilibrations following the technique of Schock and co‐workers (1980). The pH instrument was standardized daily using a two‐ or three‐point calibration with pH 4, 7, and 10 high‐precision standard solutions 1 .…”
Section: Methodsmentioning
confidence: 99%
“…While variability within a study is unavoidable, proper design and operating conditions can achieve reasonable control over water quality and material variables. Schock and Lytle (1994) highlighted the importance of proper measurements and control over certain water quality parameters (pH and dissolved inorganic carbon‐DIC) that have a significant impact on lead leaching over the course of a study.…”
Section: Discussionmentioning
confidence: 99%